A Study about the Use of Co or Mn-Based Nanocatalysts for Styrene Epoxidation Reaction - Rossi Fernández, Lucía Inés (2021)
A new catalytic system consisting of Mn or Co nanoparticles supported on different materials (celite, zeolite, activated carbon, CeO2, ZnO, MgO, Nb2O5) have been studied for styrene epoxidation. The catalysts were easily prepared from commercially available starting materials. Reaction conditions were optimized by testing different solvents, reaction temperatures, oxidizing agents, and optimal catalyst loading. CoNPs/MgO and TBHP as a co-oxidant, in refluxing ACN, allowed total conversion to the epoxide with excellent yield and high selectivity.